(untitled) (International Journal of Food and Nutritional Sciences, 2020)
Digital imaging and communication technologies have become integral components of various sectors, including healthcare, multimedia, and surveillance. However, the widespread adoption of these technologies has also brought forth numerous security challenges. The need to protect sensitive data, prevent unauthorized access, and ensure the integrity and confidentiality of digital images and communications has led to the development of various algorithmic approaches for enhancing security. This paper presents a review of multilevel algorithmic approaches aimed at addressing security concerns in digital imaging and communication systems. The multilevel approach involves combining multiple algorithms or techniques to create a robust security framework. The review begins by discussing the fundamental security requirements in digital imaging and communication systems, including authentication, encryption, watermarking, and tamper detection. It then explores the challenges posed by emerging technologies such as cloud computing, Internet of Things (IoT), and wireless communication, which necessitate advanced security measures. Subsequently, the review provides an in-depth analysis of various multilevel algorithmic approaches for digital imaging and communication security. It covers techniques such as hybrid encryption, steganography, visual cryptography, and biometric-based authentication. Each approach is examined in terms of its strengths, weaknesses, and applicability to different security scenarios.